2022
DOI: 10.3390/antiox11020399
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Hydrolysis and Drying Conditions to Whey Protein Hydrolysate Characteristics and In Vitro Antioxidative Properties

Abstract: During the generation of functional food ingredients by enzymatic hydrolysis, parameters such as choice of enzyme, reaction pH and the drying process employed may contribute to the physicochemical and bio-functional properties of the resultant protein hydrolysate ingredients. This study characterised the properties of spray- (SD) and freeze-dried (FD) whey protein hydrolysates (WPHs) generated using Alcalase® and Prolyve® under pH-stat and free-fall pH conditions. The enzyme preparation used affected the physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
0
9
0
1
Order By: Relevance
“…It was consistent with the result that the moisture content of freeze-dried chicken hydrolysate was higher than that of spray-dried [ 21 ]. In contrast, Kleekayai et al [ 23 ] observed that the moisture content of spray-dried whey protein hydrolysate was higher than that of freeze-dried whey protein hydrolysate. This may be related to the spray drying parameters employed, such as inlet and outlet temperatures, feed concentration, and airflow rate, which may affect the moisture content of SD powders [ 24 ].…”
Section: Resultsmentioning
confidence: 95%
“…It was consistent with the result that the moisture content of freeze-dried chicken hydrolysate was higher than that of spray-dried [ 21 ]. In contrast, Kleekayai et al [ 23 ] observed that the moisture content of spray-dried whey protein hydrolysate was higher than that of freeze-dried whey protein hydrolysate. This may be related to the spray drying parameters employed, such as inlet and outlet temperatures, feed concentration, and airflow rate, which may affect the moisture content of SD powders [ 24 ].…”
Section: Resultsmentioning
confidence: 95%
“…In another study, the hydrolysates of stripped weakfish were microencapsulated in maltodextrin by spray‐drying, and it was found that the type of hydrolysate (with Alcalase or Protamex) influences the production efficiency (73–76%), moisture content (5.3–6.1%), and Aw (0.11–0.13) of the powders, and the hygroscopicity of the hydrolysates decreases from 30 to 16.1–17.1%, after encapsulation (Lima et al, 2021). It has been reported that the physicochemical, functional, and flowability characteristics of encapsulated hydrolysate powders are influenced by the composition of formulation (especially, type and concentration of hydrolysate and carrier) and the microencapsulation technique (e.g., spray‐ or freeze‐drying) (Akbarbaglu et al, 2019; Gan et al, 2020; Kleekayai et al, 2022; Sarabandi & Jafari, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Lima et al, 2021). It has been reported that the physicochemical, functional, and flowability characteristics of encapsulated hydrolysate powders are influenced by the composition of formulation (especially, type and concentration of hydrolysate and carrier) and the microencapsulation technique (e.g., spray-or freeze-drying)(Akbarbaglu et al, 2019;Gan et al, 2020;Kleekayai et al, 2022; …”
mentioning
confidence: 99%
“…The highest value was found in CHP, while the lowest value was found in CHP3, namely protein hydrolysate using 0.75% bromelain and 0.25% papain. A decrease in pH after hydrolysis was also reported to occur in undersized crawfish minced meat hydrolysate (Bonilla et al, 2022) and whey protein hydrolysate (Kleekayai et al, 2022). The decrease in pH after hydrolysis may be caused by the release of carboxyl groups from protein chains during the hydrolysis process by proteases (Banjongsinsiri et al, 2016).…”
Section: Ph Of Chicken Head Protein Hydrolysatementioning
confidence: 92%